Market knowledge as a driver of SME digital marketing success in enhancing business performance - Rahman, Sarli (BISMA (Bisnis dan Manajemen), 2026)
This study examines the role of market knowledge in shaping the effectiveness of digital content marketing and social media strategies in Indonesian SMEs. While previous research has linked both market knowledge and digital marketing to business performance, their interaction is still under-researched, especially in emerging markets. Using empirical data from 370 SMEs and utilising PLS-SEM as a data analysis technique, the study shows that market knowledge alone does not directly improve performance and can even have a negative impact if it is not translated into actionable marketing practises. The findings highlight digital content and social media marketing as critical facilitators that convert knowledge into measurable results.